AN INSIGHT INTO INTERNET-ASSISTED INDEPENDENT TRAVEL (IAIT): From the tourist's perspective - LI, MIN (2007)
This research project aims to understand the general development of independent dynamic packaged holidays arranged and booked through the Internet (Internet-assisted independent travel (IAIT)) as well as understand the issues of consumer (tourist) motivation and decision making factors behind their preference of the IAIT.